Electrical measurements on the 2503 m Dome F Antarctic ice core - Fujita, Shuji; Azuma, Nobuhiko; Motoyama, Hideaki; Kameda, Takao; Narita, Hideki; Fujii, Yoshiyuki; Watanabe, Okitsugu (International Glaciological Society, 2002)
journal article